2011
DOI: 10.1007/s00122-011-1746-x
|View full text |Cite
|
Sign up to set email alerts
|

Introgression and pyramiding into common bean market class fabada of genes conferring resistance to anthracnose and potyvirus

Abstract: Anthracnose and bean common mosaic (BCM) are considered major diseases in common bean crop causing severe yield losses worldwide. This work describes the introgression and pyramiding of genes conferring genetic resistance to BCM and anthracnose local races into line A25, a bean genotype classified as market class fabada. Resistant plants were selected using resistance tests or combining resistance tests and marker-assisted selection. Lines A252, A321, A493, Sanilac BC6-Are, and BRB130 were used as resistance s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…NIL derived from the anthracnose resistance sources A493 and A321 carried an introgressed common region at the beginning of chromosome Pv04. This position agrees with results that indicated that these NIL have resistance genes in the Co‐3 cluster (Ferreira et al, 2012; Méndez‐Vigo et al, 2005) and corroborated the physical positions of the linked markers Pv‐ctt001 and SW12. The data from a Genome‐Wide Association Study (GWAS) involving 230 Andean beans indicated that the resistance to races 7 and 109 also resides in the physical position 0.21 to 0.53 Mb of chromosome Pv04 (Zuiderveen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…NIL derived from the anthracnose resistance sources A493 and A321 carried an introgressed common region at the beginning of chromosome Pv04. This position agrees with results that indicated that these NIL have resistance genes in the Co‐3 cluster (Ferreira et al, 2012; Méndez‐Vigo et al, 2005) and corroborated the physical positions of the linked markers Pv‐ctt001 and SW12. The data from a Genome‐Wide Association Study (GWAS) involving 230 Andean beans indicated that the resistance to races 7 and 109 also resides in the physical position 0.21 to 0.53 Mb of chromosome Pv04 (Zuiderveen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In Spain, for example, with this aim of local and cultural adaptation, new improved materials have been developed from landraces in tomatoes (Casals et al, 2010; Garcia-Martínez et al, 2011), beans (Bosch et al, 1998; Almirall et al, 2010; Ferreira et al, 2012), onions (Simó et al, 2012), and eggplants (Prohens et al, 2009). It would be difficult to argue that these cultivars should not be considered landraces because they have been obtained using breeding techniques like directed crossings and/or self-fertilization followed by selection.…”
Section: Landraces the New Generationmentioning
confidence: 99%
“…The gene pyramiding approaches of this study complements that of Ragagnin et al (2009) who succeeded using random amplified and polymorphic DNA (RAPD) and sequence-characterized amplified regions (SCAR) markers to pyramid resistance genes Co-4, Co-6, and Co-10 against anthracnose, Phg-1 against angular leaf spot, and Ur-ON for rust into the susceptible 'carioca' market class cultivar Rudá. Ferreira et al (2012) used SCAR, CAPS, and RAPD markers to successfully pyramid Co-2, Co-3/9 anthracnose and I and bc-3 common mosaic virus resistance genes into the 'fabada' market class A25 genotype. Ddamulira et al (2015) reported the effectiveness of gene pyramiding in improving angular leaf spot resistance in susceptible common bean cultivar.…”
Section: Gene Pyramiding and Cultivar Developmentmentioning
confidence: 99%
“…In soybean for mosaic virus disease resistance (SMV), researchers successfully pyramided three genes Rsv1, Rsv3 and Rsv4 with the aid of microsatellite markers in order to develop new soybean lines containing multiple resistance genes for soybean mosaic virus (SMV) resistance. Marker-assisted selection (MAS) and gene pyramiding have been reported in common bean research (Kelly et al, 2003, Miklas et al, 2006Ragagnin et al, 2009); Ferreira et al, 2012;. Recently, Ddamulira et al, (2015) reported the efficiency and effectiveness of gene pyramiding in improving angular leaf spot resistance in susceptible common bean cultivar.…”
Section: Introductionmentioning
confidence: 99%